Learning Impact of Armed Forces Medical Background on Military Nursing Students in an Accelerated Bachelor of Science in Nursing Program. - Wiersma, Gretchen Michele; Wilson Cox, Catherine; McNelis, Angela M.; Tebbenhoff, Billinda; Schumann, Mary Jean; Maring, Joyce (Nursing Education Perspectives (Wolters Kluwer Health))
The study examined differences between military students enrolled in an accelerated bachelor of science in nursing (BSN) program with and without medical experience and/or a previous bachelor's degree on graduation grade point average (GPA) and NCLEX®-RN first-time pass rates. Significant differences were found between groups with/withoutmilitary medical experience on NCLEX-RN, but not graduation GPA. Significant differences were found between groups with/without prior degree on GPA, but not on NCLEX-RN. Having both medical experience and a prior degree did not make a difference on GPA or NCLEX-RN. Findings offer guidance on admission criteria to accelerated programs for this unique group of students.